Effect of Prompts for Restructuring Oral Muscular Phonetic Targets (PROMPT) on Compensatory Articulation in Children With Cleft Palate/Lip. (May 2019) - Herreras Mercado, Raúl; Simpson, Kenneth; Bellom-Rohrbacher, Kristen H.
Objective . This investigation researched the effectiveness of the PROMPT (Prompts for Restructuring Oral Muscular Phonetic Targets) method to address compensatory articulation errors in children with cleft palate. Design . Single-subject AB multiple baselines across participants and behaviors. Setting . Pediatric outpatient rehabilitation department in a local hospital in a metropolitan city. Participants . The investigation consisted of 3 participants (ages = 4:4 to 12:8) born with bilateral complete cleft lip and palate. All participants underwent several reconstructive surgeries to repair their lips and palates. Interventions . The PROMPT treatment was provided for 45 minutes 3 times a week for 4 weeks (3 weeks for Participant 2). Main Outcome Measure . Therapy sessions addressed anterior lingual speech motor phonemes across 3 tiers (syllables, words, and phrases). Results . Direct visual observation of data obtained throughout this investigation indicate potential positive effects and significant correlation between improvements in sound production at 3 tiers and the implementation of the PROMPT technique. Speech intelligibility was judged by 3 blinded listeners who were unfamiliar with children with speech disorders or with cleft palate speech. All listeners identified and judged improvement in overall speech intelligibility over the course of this investigation. Listeners examined speech samples selected from sessions 3, 6, 9, and 12. Conclusion . The findings in this investigation provide a potential relationship on the effectiveness of the PROMPT method and attainment of accurate speech productions in children with cleft palate producing compensatory articulation errors, resulting in improvement in overall speech intelligibility.